First description of the male and additional data on the female morphology of Aprostocetus rubi Graham (Hymenoptera: Chalcidoidea: Eulophidae) - Jałoszyński, Paweł (Zootaxa, 2016)
The previously unknown male of Aprostocetus rubi Graham (Eulophidae: Tetrastichinae) was reared, together with females, from galls of the raspberry gall midge Lasioptera rubi (Schrank) (Diptera: Cecidomyiidae) collected in Central Poland. The male is described and illustrated for the first time, and additional information provided on the morphology of the female.